A parallelized particle tracing code for CFD simulations in Earth sciences - Manea, Vlad Constantin; Manea, Marina; Pomeran, Mihai; Besutiu, Lucian; Zlagnean, Luminita (Acta Universitaria, 2012)
The problem of convective flows in a highly viscous fluid represents a common research direction in Earth sciences. For tracing the convective motion of the fluid material, a source passive particles (or tracers) that flow at a local convection velocity and do not affect the pattern of flow it is commonly used. Here we present a parallelized tracer code that uses passive and weightless particles with their position computed from their displacement during a small time interval at the velocity of flow previously calculated for a given point in space and time. The tracer code is integrated in the open source package CitcomS, which is widely used in the solid earth community (www.geodynamics.org). We benchmarked the tracer code on the state-of-the-art CyberDyn parallel machine, a High Performance Computing (HPC) Cluster with 1344 computing cores available at the Institute of Geodynamics of the Romanian Academy.